1979
DOI: 10.1002/app.1979.070230802
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of adsorption and partition to the separation mechanism in gel chromatography on inorganic carriers

Abstract: SynopsisGel permeation chromatography (GPC) calibration curves log hydrodynamic volume versus elution volumes were obtained from a series of single and mixed eluents for polystyrene on inorganic carriers. The observed calibration shifts were interpreted as a result of adsorption and partition effects on elution volume V,. Secondary contributions to the separation mechanism can be qualitatively described by means of thermodynamic relations from liquid adsorption (LSC) and liquid partition (LLC) chromatography u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 8 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Due to partial miscibility of most liquids, which results in the "column bleeding", this kind of phase systems was practically abandoned in the liquid chromatography of small molecules soon after introduction of the high performance procedures. A quasi-stationary liquid phase for the enthalpic partition may be formed by a layer of the mixed mobile phase adsorbed on the surface of a solid column packing [29]. Due to preferential sorption effects, this layer has usually an altered composition compared to eluent.…”
Section: S-48mentioning
confidence: 99%
“…Due to partial miscibility of most liquids, which results in the "column bleeding", this kind of phase systems was practically abandoned in the liquid chromatography of small molecules soon after introduction of the high performance procedures. A quasi-stationary liquid phase for the enthalpic partition may be formed by a layer of the mixed mobile phase adsorbed on the surface of a solid column packing [29]. Due to preferential sorption effects, this layer has usually an altered composition compared to eluent.…”
Section: S-48mentioning
confidence: 99%
“…The differentiation of Equation (2) and (5) and the substitution in Equation (4), yields for the elastic chemical potential of the solvent:…”
Section: Introductionmentioning
confidence: 99%
“…However, recent work has shown that pure, entropycontrolled size exclusion occurs in far fewer cases than previously thought, especially for small molecules (26)(27)(28)(29)(30), and that a completely satisfactory elucidation of the SEC mechanism has yet to be demonstrated. So, in the light of these studies, the classical definition of size-dependent elution will have to be considered somewhat arbitrary in the absence of rigorous thermodynamic evidence.…”
Section: Resultsmentioning
confidence: 96%